BUDAYA KOMUNALISTIK HAK KEKAYAAN INTLEKTUAL TERHADAP HAK INDIKASI GEOGRAFIS SALAK PONDOH DI KABUPATEN SLEMAN - Susilo Budi Winarno (Journal of Tourism and Economic, 2018)
This study aims to determine the existence of the Geographical Indications of Salak Pondoh farmers in the Pondoh Sleman Salak Farmer Community. This community functions as a protection agency, quality improvement, and marketing of Sleman Pondoh Salak, then with the protection of Geographical indications on products from the presence of potential geographical indications can guarantee legal certainty over the products. Intellectual Property Rights (IPR) are very important issues both nationally and internationally. Pondoh Sleman Salak as an agricultural product that has distinctiveness and high quality which is developed with a communalistic system which is shown by the management of Sleman Pondoh Zalacca through Sleman Pondoh Salak Farmer Association and the Turindo Partners Association. This is the incarnation of a combination of village farmer groups (gapoktandesa) in Sleman. Then, the combination of the village farmer groups is the incarnation of the village farmer group (Poktan-dusun) which is spread in the Sleman region. In this study the method used was non random sampling to select sample subjects from the population, namely all parties related to geographical indications on pondoh salak in Sleman Regency. The data used in this study are primary and secondary data. Primary data is obtained directly through interviews with respondents. Secondary data is obtained from the study of literature on legal materials. This research is expected to contribute ideas for improving and developing legal science in the field of Geographical Indications, and can provide a more advanced thinking insight for the government and businessmen of pondoh salak in Sleman Regency to get a way out and legal certainty of violations in the field Intellectual Property Rights and Geographical Indications.Keywords: Communalistic Culture, Intellectual Property Rights Geographical Indication of Sleman Pondoh Salak, Legal Certainty